2008
DOI: 10.1159/000157880
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia and Ischemic Stroke

Abstract: There are no conclusive data regarding the association between dyslipidemia and the risk of ischemic stroke (IS). Clinical investigations have primarily focused on the association between elevated levels of low-density lipoprotein cholesterol and low levels of high-density lipoprotein cholesterol as stroke risk factors. Much less scientific attention has been aimed at elevated levels of triglycerides. Consequently the potential role of hypertriglyceridemia as an independent risk factor for IS remains controver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 74 publications
2
30
0
Order By: Relevance
“…Furthermore, it seems likely that treatment of hypertriglyceridemia may reduce the risk of ischemic stroke [14,15]. Various mechanisms of hypertriglyceridemia promoting atherosclerosis and thrombogenecity including endothelial dysfunction, oxidative stress, impaired endothelium-derived vasodilation, increased blood viscosity and fibrinogen level have been suggested [16]. However, the impact of hypertriglyceridemia in acute stroke is not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it seems likely that treatment of hypertriglyceridemia may reduce the risk of ischemic stroke [14,15]. Various mechanisms of hypertriglyceridemia promoting atherosclerosis and thrombogenecity including endothelial dysfunction, oxidative stress, impaired endothelium-derived vasodilation, increased blood viscosity and fibrinogen level have been suggested [16]. However, the impact of hypertriglyceridemia in acute stroke is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Microcirculatory disturbances may be another plausible mechanism [18]. Therefore, even though there are still some debates, we can postulate that hypertriglyceridemia could induce prothrombotic state, and eventually disturb microcirculation, especially for the vulnerable small-caliber penetrating arteries [16]. Finally, it could lead to extension of infarct or acceleration of neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many reports have also shown that hypertriglyceridemia is a risk factor for cerebral infarction, although this association is weaker than that observed for CAD 39,41,[47][48][49] . Considering these findings, these guidelines define a TG level of ≥ 150 mg/dL as the cutoff value for screening for hypertriglyceridemia; however, hypertriglyceridemia often reflects other pathological conditions, such as increased levels of • If the TG level is ≥ 400 mg/dL or non-fasting blood is used, the non HDL-C (TC−HDL-C) level should be used.…”
Section: )mentioning
confidence: 94%
“…Although environmental and clinical risk factors (such as hypertension, diabetes mellitus, hyperlipemia, atherosclerosis, smoking, excessive alcohol drinking, and so on) are considered important [3,4], nowadays a growing spectrum of genetic susceptibility factors have been identified [5,6]. With the help of robust genome-wide association studies, the biological plausibility and epidemiological evidence suggest that the elevated triglyceride (TG) level potentially contributes to an increased risk for ischemic stroke [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%